KAJIAN PERUBAHAN GARIS PANTAI MENGGUNAKAN DATA SATELIT LANDSAT DI KABUPATEN KENDAL - Arief, Muchlisin; Winarso, Gathot; Prayogo, Teguh (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2011)
Indonesia has the second longest of coastal line in the world. The change of coastal line is generated by sediment transport from the upland and the sea or generated by coming energies of sea current and wave. Coastal line change have been analyzed by multi-temporal analysis using Landsat Series Satellite (MSS, TM and ETM+). Visual interpretation of RGB 542 was done to identify coastal line, and using other combination if necessary. Based on analysis of Landsat data the coastal lines length on 1972, 1991, 2001 and years 2008 was 43.172 m, 52.646 m, 50.171 m, 53.827 m, respectively, and the change of coastal lines occurred dominant along the capes and the bays and the other places was not significantly changed. Based on Landsat satellite data analysis, in 1972 to 1991 period the abrasion and accretion occurred on 765,14 ha and 356,00 ha area, in 1991 to 2001 period were 90,64 ha and 261,89 ha, in period 2001 to 2008 were 111,67 ha and 80,37 ha.